Detection and Prevalence of Metallo-Beta- Lactamase (MBL) Enzymes Producing Pseudomonas aeruginosa Isolated from Various Clinical Samples: A Microbiological Assessment - Qureshi, Mohammed Ansar (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Background: Pseudomonas aeruginosa is a significant Gram-negative pathogen responsible for various opportunistic infections and nosocomial outbreaks. The rising incidence of hospital-acquired infections caused by P. aeruginosa, particularly those producing metallo-\(β\)-lactamases (MBLs), poses a major clinical challenge. The mechanism of resistance to beta-lactam antibiotics includes the production of beta-lactamase, reduced outer membrane permeability, the altered affinity of target penicillin-binding proteins and plasmid-mediated resistance involving modifying enzymes. Carbapenems, often considered the last-resort antibiotics for multidrug-resistant bacterial infections, are increasingly compromised due to the emergence of MBL-producing P. aeruginosa. Aim: This study aimed to detect MBL-producing P. aeruginosa isolates from clinical samples. Methods: Clinical P. aeruginosa strains were isolated and identified using standard microbiological techniques. Antimicrobial susceptibility testing was performed according to the Clinical and Laboratory Standards Institute (CLSI) guidelines (2011). Carbapenem-resistant strains were screened for MBL production using the disc potentiation test, with confirmation based on enhanced inhibition zones around imipenem and meropenem discs supplemented with EDTA. Results: Out of 120 clinical samples, the highest prevalence of MBL-producing isolates was observed in endotracheal aspirates (36.66%), followed by wound swabs (28%) and blood samples (28%). Among these, 36 (30%) isolates were carbapenem-resistant, and 22 (18.33%) tested positive for MBL production. The high prevalence of MBL-producing P. aeruginosa among multidrug-resistant strains highlights the need for early detection to optimize treatment and prevent nosocomial transmission. Conclusion: Continuous surveillance for MBL-producing P. aeruginosa is essential to mitigate the spread of resistance and ensure effective clinical management.